Mapping Research on Digital Leadership Models in Education: A Bibliometric Analysis and Future Research Directions - Cece Sutia; Djaman Satori; Aan Komariah; Asep Suryana (Universitas Negeri Malang, 2025)
Abstract: One crucial aspect of digital leadership is the professional development of teachers through Professional Learning Community (PLC). However, literature exploring the relationship between digital leadership and PLC remains limited. This study aims to analyze research trends and developments in digital leadership and its implications for teachers' professional development using bibliometric analysis. Literature data were collected from the Scopus database for the period 2020–2024 using a Boolean Search query with keywords related to digital leadership and PLC. After filtering, 3,487 articles from various countries were selected. The analysis was conducted using VOSviewer software to identify research patterns and term network mapping. The visualization results reveal four major clusters in digital leadership research: (1) school leadership and teacher professional development, (2) experimental research and mental health in education, (3) community-based learning and qualitative research, and (4) digital transformation and transformational leadership. These findings indicate that digital leadership not only supports teacher professional development but also relates to mental well-being, innovation in community-based learning, and organizational adaptation to digital transformation. This study contributes by identifying research gaps in digital leadership and PLC and providing future research directions to explore technology-driven leadership strategies to enhance teacher professional development. Keywords: Digital Leadership, Professional Learning Community, Bibliometric Analysis, Teacher Professional Development, VOSviewer